ETIKA BISNIS DALAM PERSPEKTIF HUKUM ISLAM (STUDI KASUS PADA SWALAYAN KOTA SIGLI) - Mariana Mariana; Muhammad Murthaza (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This study aims to determine the application of business ethics in Sigli citysupermarkets and business ethics practices in the Sigli City supermarket accordingto Islamic law. The research method used in the compilation of this thesis isqualitative, in obtaining data in the field the author uses several methods, namelyusing the library research method (library research), as well as field researchmethods (field research), namely by using interview techniques, documentation,and observation. The results of the study show that the application of businessethics to the Sigli City supermarket with a sample of Makmur Mark, Laut EmasMarket, and Pelita Mark has been good even though it is still not fully, at leastsupermarket owners know Islamic based business ethics where the priority ishonesty, trustworthiness, and quality. And the owner of Prosperous Mark is alsovery eager to invite all supermarket owners or managers to implement businessethics by Islamic law so that this becomes a healthy competition. The legalanalysis of business ethics practices in Sigli City supermarket not all supermarketsin Sigli city apply business ethics by sharia, but the application of business ethicsat the Prosperous Makmur Mark, Laut Emas Market, and Pelita Mark hasreflected Islamic business ethics.